Implementing Zero Trust Architectures: A Systematic Review of Benefits and Drawbacks - Gil Villa, Alex Fidel (2025)
Given the constant evolution of digital threats and the inherent limitations of traditional security approaches, Zero Trust Architectures (ZTA) have been developed as an alternative aimed at strengthening the protection of digital environments through continuous verification and contextual access control. This study systematically synthesizes and analyzes the quantifiable benefits, technical limitations, organizational challenges, proposed solutions, and evaluation metrics associated with the implementation of ZTA, considering the technical, cultural, and structural factors that influence its adoption. Through a systematic review conducted in specialized academic databases, twenty articles were analyzed following a rigorous filtering process. The results reveal significant improvements in security posture and a reduction in attack risk, driven by microsegmentation and continuous authentication; however, limitations were identified related to insufficient training, operational complexity in multicloud environments, and organizational resistance to change. It is concluded that the effectiveness of ZTA depends on its strategic integration with standardized frameworks and adequate change management within organizations.